The Effect Job Analysis and Workload Analysis of performance of Regional Civil Service Agency In west Java Province - Triyanto Triyanto; Sampara Lukman; Kusworo Kusworo (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
Job Analysis and Workload Analysis have a very important role in shaping and improving the quality and quantity of employee performance. Because it has this important role, this study directs its study of how to improve employee performance through Job Analysis and Workload Analysis. This study aims to prove and explain the effect of Job Analysis and Workload Analysis on employee performance at the Regional Personnel Agency West Java Province. The study population was all employees of the Regional Personnel Agency as many as 121 respondents. The sample in this study was selected using the proportionate stratified random sampling method of 93 respondents. Data collection through the distribution of questionnaires using a Likert scale with statistical analysis using Multiple Linear Regression. The results showed that: (1) Job Analysis had a positive and significant direct effect on the performance of West Java Provincial BKD employees by 0.508 (50.8%) the first hypothesis was proven to be significant, so the better the position analysis the better the employee performance, (2) Load Analysis Work positive and significant direct effect on employee performance of 0.183 (18.3%), the second hypothesis proved significant so the better the workload analysis the employee performance increases, (3) Job Analysis and Workload Analysis are proven simultaneously (together) affect the performance of employees by 0.402 (40.2%) the third hypothesis proved significant so that the better the Job Analysis and Workload Analysis will be able to improve the Employee Performance of the Regional Civil Service Agency of West Java Province.